2008
DOI: 10.1016/j.ejvs.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis May Increase the Risk of Peripheral Arterial Disease

Abstract: This study suggests that periodontitis may be associated with an increased risk of PAD. This association could result from the increased concentration of serum inflammatory cytokines in those with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 35 publications
3
124
0
3
Order By: Relevance
“…Jurisic et al reported that the concentration of TNF-α is signifi cantly increased in radicular cysts in terms of cyst wall thickness, count of infl ammatory cells, degree of vascularization per mm 2 and other epithelial characteristics [25]. In contrast, other studies have detected no increase in the TNF-α level in the serum of patients with periodontitis [26]. Therefore, the suppression of TNF-α release and increase of IL-10 production may protect tissues in the infl ammation focus [27].…”
Section: Discussionmentioning
confidence: 98%
“…Jurisic et al reported that the concentration of TNF-α is signifi cantly increased in radicular cysts in terms of cyst wall thickness, count of infl ammatory cells, degree of vascularization per mm 2 and other epithelial characteristics [25]. In contrast, other studies have detected no increase in the TNF-α level in the serum of patients with periodontitis [26]. Therefore, the suppression of TNF-α release and increase of IL-10 production may protect tissues in the infl ammation focus [27].…”
Section: Discussionmentioning
confidence: 98%
“…39 Examples include interleukin 1 beta (IL 1β), IL-6, tumor necrosis factor alpha (TNF-α), CRP and neutrophils. 41,42 Chronic inflammation associated with bacterial plaque is predominantly caused by gram-negative bacteria. After the inflammatory stimulus there is increased production of prostaglandin E2 (PGE2) and of matrix metalloproteinases (MMP), which lead to extracellular destruction of the gingiva and the periodontal ligament, stimulating resorption of alveolar bone.…”
Section: Pathophysiology Of Periodontal Diseasementioning
confidence: 99%
“…There is then recruitment of monocytes, and increase in expression of endothelial adhesion molecules and increased uptake of lipids by macrophages. 41 The bacterial agents most frequently identified in atherosclerotic plaques are Porphyromonas gingivalis (32%); Aggregatibacter actinomycetencomitans (4%); Prevotella intermédia (20%), and Treponema denticola (32%). Administration of systemic antibiotics to patients with periodontitis resulted in reductions in the levels of systemic markers of inflammation.…”
Section: Pathophysiology Of Periodontal Diseasementioning
confidence: 99%
“…In particular, studies have reported the relationship between periodontal disease and CVD based on incidence or mortality [3,4]. Continuing studies [5][6][7][8] have revealed that periodontal disease is another important risk factor for cardiovascular diseases. The host-mediated inflammatory response to periodontal pathogens and their components, release of matrix metalloproteinases, alteration in lipoprotein metabolism and poor dietary habits may contribute to the atheroma pathogenesis in patients with periodontal disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the total number of WBC in peripheral blood has been used as a diagnostic measure to investigate whether a given individual suffers from an infection or inflammatory disease [11]. Studies have reported the relation between periodontal disease and inflammatory markers including CRP level [7][8][9][10][11][12][13][14][15][16][17] and WBC count [18,19]. Additionally, many clinical periodontal parameters were included, such as the number of missing teeth, clinical attachment level (CAL), periodontal probing depth (PD) and bleeding on probing (BOP), to determine the effect on systemic biomarkers, respectively.…”
Section: Introductionmentioning
confidence: 99%